Health Education Using Health Belief Model for Early Mobilization and Pain Post-Cesarean: A Literature Review - Ekabudiningsih, Vinda; Susanti, Ni Luh Putu Dina; Diyu, Ida Ayu Ningrat Pangruating; Sagitarini, Putu Noviana (Babali Publisher, 2026)
Introduction: Postoperative pain and delayed mobilization after cesarean section (CS) can prolong recovery, increase complication risks, and extend hospital length of stay. Preoperative education is a non-pharmacological strategy to improve readiness, and the Health Belief Model (HBM) offers a structured approach by targeting perceived susceptibility, severity, benefits, barriers, cues to action, and self-efficacy. This review examined how HBM-based preoperative health education influences postoperative pain and early mobilization among CS patients. Methods: A Systematic Literature Review (SLR) was conducted using Kitchenham’s stages (planning–implementation–reporting) and reported using PRISMA 2020. Searches were performed in ScienceDirect and PubMed using the terms “Health Belief Model,” “postoperative pain,” “early mobilization,” and “cesarean section.” Eligible studies were full-text articles (2020–2024), written in English or Indonesian, that applied or discussed HBM within health interventions. From 3,218 records, 17 studies met the inclusion criteria after screening. Results: Across studies, HBM-based education was associated with improved patient understanding, stronger self-efficacy, and reduced psychological barriers (e.g., fear of pain or wound disruption), which supported earlier rising and increased physical activity. Higher self-efficacy and fewer perceived barriers were consistently linked to lower discomfort and faster functional recovery. Several studies also indicated that multimedia-supported education enhanced engagement and message clarity, potentially strengthening cues to action. Conclusion: HBM-based preoperative education shows promise for supporting pain management and promoting early mobilization after CS, thereby facilitating recovery and improving care efficiency.